Selective Conversion of 2-Methylfuran to 1,4-Pentanediol Catalyzed by Bimetallic Ni-Sn Alloy - Rodiansono Rodiansono; Astuti Maria Dewi; Sadang Husain; Agung Nugroho; Sutomo Sutomo (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2019)
The selective conversion of 2-methylfuran (2-MeF) to 1,4-pentanediol (1,4-PeD) over bimetallic nickel-tin alloy catalysts in the ethanol/H2O solvent mixture was studied. By using bulk Ni-Sn(x); x = 3.0 and 1.5 catalysts, a maximum yield of 1,4-PeD (49%) was obtained at 94% conversion of 2-MeF. The dispersion of Ni-Sn(x) on the aluminium hydroxide (AlOH) or g-Al2O3 supports allowed to an outstanding yield of 1,4-PeD (up to 64%) at 433 K, 3.0 MPa of H2 within 12 h. Ni-Sn(3.0)/AlOH catalyst was found to be reusable and the treatment of the recovered Ni-Sn(3.0)/AlOH catalyst with H2 at 673 K for 1 h restored the catalyst’s original activity and selectivity.